The Red shoes - Powell, Michael; Powell, Michael; Powell, Michael; Walbrook, Anton 1896-1967; Shearer, Moira 1926-2006; Goring, Marius 1912-1998 (Hallmark Home Entertainment, 1995)
A beautiful ballerina must choose between dance and romance in this dazzling behind-the-curtain peek at the world of ballet. Moira Shearer is radiant as the young ballet star with the world at her feet, caught in a heartbreaking struggle between the gifted composer she longs for and the dance impresario she lives for.